Suppose 23 + 237 = -5*t. Let l be (39/t)/(6/(-16)). Solve -4 = -2*v - l for v.
1
Let j be -3(-3)/4-4. Let x = j - -9. Solve 3*w + 15 + x = 0 for w.
-5
Let x® = 4 + 3*r2 - 5*r2 - 3*r + 3*r**2. Let p be x(3). Suppose 4 - 12 = 3*z + p*h, 0 = -4*z - 5*h - 9. Solve 0*b + z*b - 8 = 0 for b.
2
Let j be 4⁄10 + 88/(-20). Suppose -1 = -3*b - 4. Let g = b - j. Solve 0 = -0*h - h - g for h.
-3
Suppose d = -h - d + 11, 125 = 5*h - 4*d. Suppose -z + h = 1. Suppose 0 = -2*a + 3*a - 5*j + 17, 4*j - z = 0. Solve -5*b + 17 = -a for b.
5
Let o = 85 - 70. Solve 5*j = -5 - o for j.
-4
Let q = 124 - 118. Solve 5 = -q*r + r for r.
-1
Let q(v) = -3*v - 17. Let c be q(-9). Solve 6*o - c = o for o.
2
Let z(u) = -14*u + 34*u - 13*u - 4 - 8*u. Let y = 8 + -14. Let j be z(y). Solve c + j = 2*c for c.
2
Suppose -2*h + 1 = -3. Suppose -x = -4, -b = -x + 4 - h. Solve b*y - 3*y = 1 for y.
-1